PENGARUH INFLASI, SUKU BUNGA, DAN NILAI TUKAR KURS DOLLAR (USA) TERHADAP INDEKS HARGA SAHAM LQ45 DI BURSA EFEK INDONESIA (PERIODE 2014-2018) - Andita Meilasari (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
This study aims to determine the effect of inflation, interest rates, and the exchange rate of the dollar (USA) on the LQ45 stock price index. Data collection techniques are a method of Documentation. For test instruments using classic assumption tests and tests Statistics. Data analysis techniques using some linear regression for variables using four variables, test F and test t. The results showed that variable inflation (X1), interest rate (X2), and exchange rate (X3) simultaneously LQ45 stock price index on the Indonesia Stock Exchange (Y).